Antimicrobial drug use and its association with antimicrobial resistance in fecal commensals from cows on California dairies - Abdelfattah, Essam M.; Ekong, Pius S.; Okello, Emmanuel; Chamchoy, Tapakorn; Karle, Betsy M.; Black, Randi A.; ElAshmawy, Wagdy; Sheedy, David; Williams, Deniece R.; Lehenbauer, Terry W.; Byrne, Barbara A.; Aly, Sharif S. (Frontiers in Veterinary Science, 2025)
The current study objective was to investigate the risk factors associated with the isolation of antimicrobial-resistant Escherichia coli, Enterococcus spp., and Streptococcus spp. (ES) from the feces of dairy cows in California (CA). A longitudinal study was conducted on ten dairies, and a random sample of cattle (late pregnant heifers and dry cows) stratified by each herd’s parity distribution were followed monthly from close-up to 120 days in milk during fall to winter 2018 (winter season) and spring to summer 2019 (summer season). Gastrointestinal commensals were isolated from fecal samples and tested for antimicrobial susceptibility using the broth microdilution method against a selected panel of antimicrobial drugs (AMD). Eight dairies used blanket AMD therapy at dry-off for all lactating cows, while the remaining two dairies did not use any AMD treatment at dry-off. Clinical mastitis was identified as the most common indication for AMD use across the study dairies. Intramuscular administration of ceftiofur hydrochloride to treat lameness and unknown disease during lactation was significantly associated with the isolation of tetracycline-resistant fecal E. coli. Resistance to ceftiofur, tetracycline, or trimethoprim-sulfamethoxazole in fecal E. coli was significantly higher in the winter than in the summer season. In contrast, resistance to tetracycline, florfenicol, tilmicosin, tildipirosin, or tiamulin in fecal gram-positive commensals was significantly higher in the summer than in the winter. In conclusion, AMD usage practices and seasonal variations significantly influenced the AMR of E. coli and ES in the feces of dairy cattle.